Community Empowerment Through Bamboo Laminate Technology as Part of Disaster Conservation and Mitigation in Wonokerto, Turi, Sleman, Yogyakarta - Krisdiyanto, Didik; Farihah, Tutik; Supriyati, Hikmah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Bamboo is included in the classification of grasses, but because of its large size compared to other types of grass, bamboo is also called